Alternatives to Improve Performance and Operation of a Hybrid Solar Thermal Power Plant Using Hybrid Closed Brayton Cycle (2022)
Hybrid solar thermal power plants using the Brayton cycle are currently of great interest as they have proven to be technically feasible. This study evaluates mechanisms to reduce fuel consumption and increase the power generated, improving plant efficiency. An energy and exergy model for the hybrid solar plant is developed using an estimation model for the solar resource to determine the plant operation under specific environmental conditions. The effect of using different working fluids in the Brayton cycle, such as air, and helium in transcritical conditions and carbon dioxide in subcritical and supercritical conditions, is evaluated. Additionally, the plant’s exergy destruction and exergy efficiency are evaluated. In those, it can be highlighted that the helium cycle in the same operating conditions compared to other working fluids can increase the power by 160%, increasing fuel consumption by more than 390%.